PREVALENCE OF DIABETES MELLITUS AMONG OBESE AND NON-OBESE PATIENTS WITH CORONARY ARTERY DISEASE - Khan, Sher Bahadar; Rehman, Hafiz -ur-; Noor, Lubna; Ullah, Hameed; Hafeezullah, Mohammad; Gul, Adnan Mahmood; Hadi, Abdul (Journal of Ayub Medical College Abbottabad, 2010)
Background: Globally, obesity is now recognised as an epidemic. The degree of obesity is proportional to the rate of development of cardiovascular diseases, hence, resulting in a dramatic increase in morbidity and mortality. Apart from obesity, diabetes mellitus is another well recognised risk factor contributing to coronary artery disease. The precise prevalence of obesityrelated diabetes varies with age, race and gender; and is yet unknown in our population. We therefore, carried out this study with the aim to determine the prevalence of diabetes mellitus in obese and non-obese patients with diagnosed coronary artery disease. Methods: This hospital based cross-sectional comparative study was conducted in Cardiology Department of Postgraduate Medical Institute, Lady Reading Hospital, Peshawar, from 15th March 2005 to 30th May 2006. A total of 200 patients with diagnosed coronary artery disease were enrolled, 100 were classified as obese and 100 as non-obese. Results: Among these, 139 patients were male and 61 female. A total of 88 were found to be diabetic, 54 of these were obese and 34 non-obese (p=0.004). Conclusion: Diabetes mellitus was significantly more frequent among obese patients with coronary artery disease as compared to non obese patients with coronary artery disease. Keywords: Coronary Artery Disease, Body Mass Index, Obesity, Diabetes Mellitus